The Relationship Between Fast Food Consumption and Obesity Among Adults at Pekan Labuhan Health Center, Medan, Indonesia - Samosir, Fauzan Azmi Hasti Habibi; Qalbi, Kamila Harisah; Wijaya, Vincent; Kathy, Kathy; Miadi, Yesindi Nakita; Putri, Monica Dwi; Harahap, Juliandi (Universitas Airlangga, 2025)
Obesity is defined as an excessive accumulation of body fat resulting from a prolonged imbalance between energy intake and energy expenditure, which may lead to various physical and psychosocial health complications. In Indonesia, the prevalence of adult obesity has reached approximately 22%, affecting around 625,000 individuals. One primary contributing factor to weight gain is the frequent consumption of high-calorie foods, such as sugary beverages, fast food, and items with a high glycemic index. This study investigated the association between fast food consumption and obesity among adults. An analytical cross-sectional study involved adult participants at the Pekan Labuhan Community Health Center in Medan who met specific inclusion and exclusion criteria. Data were obtained through structured interviews to assess the frequency of fast food consumption, alongside anthropometric measurements, including body weight, height, and calculation of Body Mass Index (BMI). The results indicated that 63% of the adult population in this community health center were classified as obese, and 72% reported frequent fast food consumption. Statistical analysis using the Pearson correlation test demonstrated a significant relationship between fast food consumption and obesity (p=0.001). The findings suggest that a higher frequency of fast food intake is significantly associated with increased obesity risk. These results underscore the importance of dietary education and public health strategies aimed at reducing fast food consumption to combat the rising prevalence of obesity.